Adherence to disease-modifying therapies and its impact on relapse, health resource utilization, and costs among patients with multiple sclerosis - Burks J; Marshall TS; Ye X (Dove Medical Press, 2017)
Jack Burks,1 Thomas S Marshall,2 Xiaolan Ye2 1Nova Southeastern University, Davie, FL, 2AbbVie Inc, Chicago, IL, USA Purpose: To evaluate adherence to disease-modifying therapies (DMTs) among patients with multiple sclerosis (MS) initiating oral and injectable DMTs, and to estimate the impact of adherence on relapse, health resource utilization, and medical costs.Patients and methods: Commercially insured MS patients (aged 18–65 years, two or more MS diagnoses, one or more DMT claims) with continuous eligibility 12 months before and after the first DMT claim date (index date) and no DMT claim during the pre-index period were identified from a large commerical claims database for the period from January 1, 2008, to September 30, 2015. Adherence to the index DMT was measured by the 12-month post-index proportion of days covered (PDC) and compared between oral and injectable DMT initiators. After adjustment for sex, age at index DMT, and comorbidities, regression models examined the relationship between adherence and relapse risk, MS-related health resource utilization, and non-drug medical costs (2015 US$).Results: The study covered 12,431 patients and nine DMTs. Adherence to the index DMT did not differ significantly between oral (n=1,018) and injectable (n=11,413) DMTs when assessed by mean PDC (0.7257±0.2934 vs 0.7259±0.2869, respectively; P=0.0787), or percentages achieving PDC ≥0.8 (61.4% vs 58.6%, respectively; P=0.0806). Compared to non-adherence, adherence to DMT significantly reduced the likelihood of relapse in the post-index 12 months by 42%, hospitalization by 52%, and emergency visits by 38% (all, P<0.0001). Adherent patients would be expected to have on average 0.7 fewer outpatient visits annually versus non-adherent patients (P<0.0001). Based on the differences in predicted mean costs, adherence (vs non-adherence) would decrease the total annual medical care costs by $5,816 per patient, including hospitalization costs by $1,953, emergency visits by $171, and outpatient visits by $2,802.Conclusion: Adherence remains suboptimal but comparable between oral and injectable DMTs. Potential health and economic benefits underscore the importance of improving adherence in MS. Keywords: MS, DMT prescribing patterns, implications